THE CONCEPT OF DISCOURSE IN MODERN LINGUISTICS - Abdumalikova Dilfuza (Zeta Repository, 2023)
The article is devoted to the definition of the concept of discourse in linguistics through the prism different approaches with the identification of the characteristics of each. Four approaches were chosen to consider the concept of discourse: communicative, structural-syntactic, structural-stylistic and socio-pragmatic. As a result of studying these approaches, it was revealed that one side of the discourse is addressed to pragmatics, to typical situations of communication, the other to the processes taking place in the minds of the participants in communication, and the third to the text itself. This gave reason to believe that discourse can be considered both as a process and as a result in the form of a fixed text.